Enhancing Junior High School Students’ Speaking Skills through Group Based-Learning - Fahira, Prahda; Sofiana, Nina (Universitas Islam Ahmad Dahlan (UIAD), 2025)
This study investigates the effectiveness of group-based learning in enhancing the speaking abilities of eighth-grade students at SMP Muhammadiyah Keling. The school was selected due to observable challenges among students in verbal expression, including limited vocabulary, low confidence, and minimal classroom interaction. Speaking skill is a crucial aspect of language proficiency, reflecting learners’ communicative competence and playing a vital role in academic success and social integration. While previous studies have explored cooperative learning, few have examined its implementation specifically in a value-based school with limited use of interactive methods. A quantitative approach was employed using a pre-experimental one-group pre-test and post-test design involving 18 students. The intervention spanned four sessions over two weeks. Speaking skills were assessed through structured tasks measuring fluency, pronunciation, vocabulary, grammar, and content. Results showed a significant improvement in speaking performance, with the mean score rising from 65.56 to 84.44. A paired sample t-test yielded a p-value of 0.000 (p < 0.05), indicating a statistically significant difference. While the study was limited by sample size and duration, the findings suggest that group-based learning fosters peer interaction and active participation, contributing to improved oral communication. These results have practical implications for EFL instruction, particularly in promoting student-centered learning environments. Future research could explore long-term impacts and adaptations of group-based strategies across diverse educational contexts.